Implementasi Sistem Informasi Digital Marketing Berbasis Website Dengan Fitur Custom Desain Interaktif - Toriq Andana Teguh Febriansyah; Siti Sufaidah; Chairul Anam (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The rapid development of information technology encourages business actors, including the garment manufacturing sector, to adopt digital information systems in order to improve marketing effectiveness and customer service quality. Faiz Konveksi, a micro, small, and medium-sized enterprise engaged in garment production services, still faces various challenges related to marketing, design communication, ordering, and payment processes that are not yet systematically integrated. This study aims to design and implement a website-based digital marketing information system equipped with an interactive custom design feature to facilitate customers in independently customizing product designs, improve the effectiveness of design communication, and integrate ordering and payment processes into a single platform. The research method consists of needs analysis, system design, system implementation, and system testing. The developed system supports three user roles, namely customer, administrator, and super administrator, and provides key features including a product catalog, three-dimensional interactive custom design, order management, online payment services, WhatsApp notification services, and sales and order reports. The results of implementation and system testing indicate that the proposed system is able to increase ordering efficiency, reduce design communication errors, and assist Faiz Konveksi in managing order and transaction data in a more effective and structured manner. Therefore, the website-based digital marketing information system is expected to enhance service quality, customer satisfaction, and the competitiveness of Faiz Konveksi in the digital era.